Carbon Nanodots for All-in-One Photocatalytic Hydrogen Generation - Jana, Bikash; Reva, Yana; Scharl, Tobias; Strauss, Volker; Cadranel, Alejandro; Guldi, Dirk Michael (Journal of the American Chemical Society, 2021)
Carbon nanodots (CNDs) were photochemically altered to produce dihydrogen under light irradiation. Within the complex structure of CNDs, photo-oxidation takes place at citrazinic acid molecular fluorophore sites. Important is the fact that the resulting CND materials have a dual function. On one hand, they absorb light, and on the other hand, they photo- and electrocatalytically produce dihydrogen from water and seawater, without any external photosensitizer or cocatalyst. Record HER activities of 15.15 and 19.70 mmol(H2) g(catalyst)-1 h-1 were obtained after 1 h of 75 mW/cm2 Xe lamp illumination, from water and seawater, respectively. This impressive performance outweighs the remaining structural uncertainties. A full-fledged physicochemical investigation based on an arsenal of steady-state and time-resolved spectroscopic characterizations together with microscopy enabled a comprehensive look into the reaction mechanism. For an efficient dihydrogen formation, a precatalytic activation by means of reduction with a sacrificial electron donor is imperative.
CRIS-Team Scopus Importer:2021-12-24

Tartaric acid-derived chiral carbon nanodots for catalytic enantioselective ring-opening reactions of styrene oxide - Zhao, Xinyi; Reva, Yana; Jana, Bikash; Langford, Daniel; Kinzelmann, Marina; Zhang, Zhipeng; Liu, Qi; Drewello, Thomas; Guldi, Dirk Michael; Chen, Xiaoqing (Chemical Communications, 2024)
Chiral carbon nanodots (CNDs) were fabricated through the hydrothermal processing of sulfanilic acid and chiral tartaric acid, exhibiting outstanding catalytic performance for the chiral catalysis of the ring-opening reaction. Furthermore, the catalytic mechanism was proposed to understand the link between the chiral structure and the performance of the catalyst.
CRIS-Team Scopus Importer:2024-09-27

Tuning the Absorption, Fluorescence, Intramolecular Charge Transfer, and Intersystem Crossing in Spiro[fluorene]acridinone - Bo, Yifan; Zhang, He; Li, Yue; Reva, Yana; Xie, Linghai; Guldi, Dirk Michael (Angewandte Chemie International Edition, 2024)
In this work, we prepared a series of electron donor-acceptor systems based on spiro[fluorene-9,7’-dibenzo[c,h]acridine]-5’-one (SFDBAO). Our SFDBAOs consist of orthogonally positioned fluorenes and aromatic ketones. By fine-tuning the substitution of electron-donating pyrenes, the complex interplay among different excited-state decay channels and the overall impact of solvents on these decay channels were uncovered. Placing pyrene, for example, at the aromatic ketones resulted in a profound solvatochromism in the form of a bright charge-transfer (CT) emission spanning from yellow to red-NIR. In contrast, a dark non-emissive CT was noted upon pyrene substitution at the fluorenes. In apolar solvents, efficient triplet-excited state generation was observed for all SFDBAOs. Either charge transfer was concluded to mediate the intersystem crossing (ISC) in the case of pyrene substitution or the El-Sayed rule was applicable when lacking pyrene substitution as in the case of SFABAO. In polar solvents, charge separation is the sole decay upon pyrene substitution. Moreover, competition between ISC and CT lowered the triplet-excited state generation in SFDBAO.
CRIS-Team Scopus Importer:2024-03-22
Keywords: charge transfer; intersystem crossing; ketones; spiro-conjugation; triplet sensitizers

Understanding the Visible Absorption of Electron Accepting and Donating CNDs - Reva, Yana; Jana, Bikash; Langford, Daniel; Kinzelmann, Marina; Bo, Yifan; Schol, Peter; Scharl, Tobias; Zhao, Xinyi; Crisp, Ryan; Drewello, Thomas; Clark, Timothy; Cadranel, Alejandro; et al. (Small, 2023)
Carbon nanodots (CNDs) synthesized from citric acid and formyl derivatives, that is, formamide, urea, or N-methylformamide, stand out through their broad-range visible-light absorbance and extraordinary photostability. Despite their potential, their use has thus far been limited to imaging research. This work has now investigated the link between CNDs’ photochemical properties and their chemical structure. Electron-rich, yellow carbon nanodots (yCNDs) are obtained with in situ addition of NaOH during the synthesis, whereas otherwise electron-poor, red carbon nanodots (rCNDs) are obtained. These properties originate from the reduced and oxidized dimer of citrazinic acid within the matrix of yCNDs and rCNDs, respectively. Remarkably, yCNDs deposited on TiO2 give a 30% higher photocurrent density of 0.7 mA cm−2 at +0.3 V versus Ag/AgCl under Xe-lamp irradiation (450 nm long-pass filter, 100 mW cm−2) than rCNDs. The difference in overall photoelectric performance is due to fundamentally different charge-transfer mechanisms. These depend on either the electron-accepting or the electron-donating nature of the CNDs, as is evident from photoelectrochemical tests with TiO2 and NiO and time-resolved spectroscopic measurements.
Created from Fastlane, Scopus look-up
Keywords: carbon nanodots; excited state; photoelectrochemistry; semiconductors; time-resolved spectroscopy